Effect of cutting speed on milling process on surface roughness of ST-37 steel material workpiece - Budi Syahri; Febri Prasetya; Refdinal Refdinal; Syahrial Syahrial (Universitas Negeri Padang, 2021)
The importance of the surface roughness value of a workpiece must be of concern to students and machine operators because the surface roughness of the workpiece becomes a benchmark for the use of a component in the machining plane and one of the significant influences on the surface roughness of the workpiece is the cutting speed parameter. To examine the extent of the effect of cutting speed on surface roughness, testing and analysis of the machining process results were carried out by varying three cutting speeds according to the material range and the type of cutting tool used. This study uses an experimental method, with the research object using steel ST-37 by making cuts on the surface. Test result data obtained that the average roughness price per rotation speed is (Ras) = 4.01μm for Cs 20 with a rotation speed of 530.78 Rpm. (∑Ras) = 2.84μm for cs 25 with a rotation speed of 663.48Rpm. (∑Ras) = 2.59 μm for cs 30 with a rotation speed of 796.18Rpm. With the roughness grade on the N8. So the conclusion in this study is that the higher the engine rotation speed, which is influenced by high cutting speed, the lower the surface roughness of the resulting workpiece.